Linkage between universities, research institutes and enterprises in scientific and technological activities - Trang, Pham Hong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
The triple helix (tripartite links) between universities, research institutes and enterprises has important roles in efforts to push up science-technology (S&T) activities, to enhance transfer of research results. The links in S&T activities can be realized in many sectors of activities, namely: exchange of S&T human resources, cooperation of research, transfer of research results, exchange of S&T information and etc. These linking activities are being conducted in universities but there exist certain barriers in policies, research capacities and other ensuring conditions. This paper provides an analysis of the actual situation of links between universities, research institutes and enterprises, indicates some factors causing barriers to these links and then proposes some recommendations to enhance the links between the three important actors. Code: 17021401